KUMPULAN PUISI NEGERI DAGING KARYA A. MUSTOFA BISRI: ETIKA LIBERASI DAN KANDUNGAN NILAI KARAKTERNYA (METODE SASTRA PROFETIK) - Midle Line Krismonsari; Widowati Widowati (CARAKA, 2020)
The purpose of this study is to describe the ethics of liberation, values characters in the collection of Negeri Daging by A. Mustofa Bisri,, and its application in learning as a character education media. Research this is a qualitative research. Research data in the form of aesthetic unity and grammatical unity. Data source in the form of a collection of Negeri Daging. Instrument. This research is the researcher himself with the relevant theory and assisted grating along with indicators of ethical liberation and character values. Data collection technique using note taking techniques. Data analysis techniques using descriptive techniques qualitative. The results of his research are as follows. 1) Ethics of liberation include: a) Political oppression represents an authoritarian system of government, no the existence of human rights; b) State oppression depicts the absence of freedom opinion, gross human rights violations, and dictatorial leadership; c) Economic injustice illustrates social inequality, monetary crisis, corruption; and d) gender injustice illustrates harassment of people women, domestic violence, women deemed inappropriate as leaders. 2) Value characters include: tolerance, democratic, national spirit, peace, and responsible. 3) Application in learning as an educational medium characters through KI 3 and KD 3.16, 3.8 (IBB) using the method participatory-exhibition.